Application of Facies Controlled Prestack Inversion Technology in Prediction of Deep Tight Gas in Continental Faulted Basin. (25th September 2022) - Guan, Xiaowei; Meng, Qian; Jiang, Chuanjin; Chen, Xuehai; She, Rui; Sun, Lidong
Abstract : It is difficult to predict tight sandstone gas in continental rift basin because of complex deep structure, fast transformation of sedimentary facies, large lateral variation of reservoir thickness, and tight and strong heterogeneity. Based on the petrophysical analysis of logging data, this paper improved the traditional low-frequency establishment method of prestack synchronous inversion which is under the constraints of fine isochronal sequence stratigraphy framework. The prestack AVO has attributed as covariate, and Bayes kriging method has applied to establish low-frequency model. Then, the relationship between density and P-wave and S-wave impedance has been introduced. The results show that the stability of density parameters has been improved, and the facies controlled prestack inversion with drilling verification has been realized which the number of layers with thickness error less than 20% accounts for 75.2%. Exploration practice shows that the facies controlled prestack inversion technology has important reference significance for other deep continental fault basins.